SIRT3 alleviates imiquimod-induced psoriatic dermatitis through deacetylation of XBP1s and modulation of TLR7/8 inducing IL-23 production in macrophages - Guo, Meiliang; Zhuang, Haojun; Su, Yimin; Meng, Qinqin; Liu, Wanwen; Liu, Na; Wei, Min; Dai, Sheng-Ming; Deng, Hui (Frontiers in Immunology, 2023)
IL-23, IL-6 and TNF-α play pivotal roles in the pathogenesis of psoriasis. Although it is well-established that Sirtuin 3 (SIRT3) mediates the inflammatory process, the specific mechanisms remain largely unclear. Here, we report that inhibition or deletion of SIRT3 potentiated the production of IL-23a by amplifying the acetylation level of spliced form of X-box binding protein 1 (XBP1s) and its transcription activity. Inhibition or knockdown of SIRT3 could exacerbate psoriasis-like skin inflammation in an imiquimod-induced psoriasis-like mouse model. We further showed that SIRT3 decreased in macrophages of psoriatic patients, leading to increased XBP1s expression and its acetylation level. Our results provide compelling evidence of the crucial role of SIRT3 in the IL-23 axis in psoriatic inflammation and provide novel molecular insights into the anti-inflammatory effects of SIRT3.